Absolute total ionization cross sections of uracil (C4H4N2O2) in collisions with MeV energy highly charged carbon, oxygen and fluorine ions - Agnihotri, A. N. (2013)
Ionization and fragmentation of uracil molecules (C4H4N2O2, m = 112 amu) in collisions with fast highly charged C, O and F ions have been investigated using a time-of-flight mass spectrometer. The measurement of total ionization cross sections (TCS) is reported for different charge states (q), such as Fq + with q = 5–8; Oq + with q = 5,7; Cq + with q = 5 and 6. These studies reveal a (q/v)~1.5 dependence of TCS, in contrast, to the well-known q2-dependence in ion–atom collisions. Scaling properties of the TCS with projectile energy and charge states are obtained. The experimental results for TCS measurements are compared with the theoretical calculations performed within classical and quantum mechanical frameworks. The trends in energy dependence of the TCSs is qualitatively well reproduced by the different models and more specifically by the classical description, which provides the best agreement with measurements.